Impact of demographic and perioperative risk factors on complication rates in skin-sparing/nipple-sparing mastectomy with implant-based reconstruction using titanized polypropylene mesh (TiLOOP® Bra). (March 2022) - Michno, Viktoria; Malter, Wolfram; Paepke, Stefan; Thill, Marc; Kelling, Katharina; Meiré, Anette; Tofall, Sabrina; Nolte, Elke; Christ, Hildegard; Eichler, Christian
Abstract: Background: Skin/nipple-sparing mastectomies (SSM/NSSM) have been reported to have acceptable complication rates and good aesthetic outcomes with high patient satisfaction. However, in this relatively young and rapidly expanding field of reconstructive plastic surgery, differences in perioperative management are noted between breast centers. Prospective studies of complication rates using a titanized polypropylene mesh (TiLOOP® Bra) are currently lacking. Methods: A prospective subgroup analysis was performed based on the data set of the prospective, single-arm, multicenter observational study (PRO-BRA). Early complication rates after skin/nipple-sparing mastectomy with implant-based immediate or secondary reconstruction using a titanized polypropylene mesh (TiLOOP® Bra) subpectorally were investigated in relation to demographic factors, as well as intra-and postoperative management. The subgroup consists of 258 patients. Complications were categorised into necrosis, infection, postoperative bleeding or hematoma, seroma, wound healing delays and R1-situations. Results: Early complication rates of SSM/NSSM using titanium-based meshes are comparable to complication-rates using ADM's. Logistic regression shows significantly higher risk for wound healing delays, necrosis and seroma with increasing BMI, abladat- and implant-weight (OR 1, 17 -1, 66, p-value < 0, 001). Smokers have significantly higher necrosis rates (20.7%) compared to non-smokers (5.5%) (p-value = 0.002). Discharge with drainage results in a trend toward higher rates of wound healing complications. Conclusion: The use of TiLOOP® Bra meshes was shown to have acceptable complication rates. Complication rates depend on certain demographic and intraoperative risk factors and should be considered in indications and information of patients. Highlights: BMI and ablative/implant weight significantly influence complication rates of SSM/NSSM. Necrosis rates depend on smoking behavior and incision type. Single Shot antibiosis has no higher infection rates compared to prolonged antibiotic therapy. Discharging patients with drainage does not show significantly higher complication rates. Preservation of fascia pectoralis decreases seroma rates, especially in older patients with high risk for seroma.